Journal Notes - various authors (GDR Bulletin, 1982)
Reviews of: Weimarer Beiträge Vol. 27, No. 10-12 (Russell Berman) Zeitschrift für Germanistik Heft 3 and 4 (Karl-Heinz Schoeps) GDR Monitor No. 5 Deutsche Bücher Vol. 11, No. 1